Legal and Medical Aspects of Off-Label Medication Use. Point of View - O. V. Tsygankova; T. I. Batluk; L. D. Latyntseva; D. Y. Platonov; N. M. Akhmedzhanov (Рациональная фармакотерапия в кардиологии)
The current state of the Russian and foreign regulatory framework for off-label prescription of medicines is presented in the article. The existing problems of this specific drug therapy and possible solutions are described. Unfortunately, there are some gaps in the Russian legislation regarding the off-label medication use. Based on the clinical reality, in some cases, the “off-label” drugs prescription can be justified by the clinical condition of the patient, the lack of alternative approved drugs, and the availability of published scientific data that create the prerequisites for the effectiveness of this approach. When off-label drug prescribing as a forced measure, the doctor must provide a rationale for this prescription in the medical documentation, the conclusion of the consultation (with the participation of relevant specialists and the clinical pharmacologist) or the medical commission (with the participation of the administration representative), and the written informed consent of the patient or his legal representative. This information should be actively communicated to doctors in order to increase their legal literacy and prevent possible negative and legal consequences.